2015
DOI: 10.1111/tpj.13089
|View full text |Cite
|
Sign up to set email alerts
|

A pioneer protein is part of a large complex involved in trans‐splicing of a group II intron in the chloroplast of Chlamydomonas reinhardtii

Abstract: SUMMARYSplicing of organellar introns requires the activity of numerous nucleus-encoded factors. In the chloroplast of Chlamydomonas reinhardtii, maturation of psaA mRNA encoding photosystem I subunit A involves two steps of trans-splicing. The exons, located on three separate transcripts, are flanked by sequences that fold to form the conserved structures of two group II introns. A fourth transcript contributes to assembly of the first intron, which is thus tripartite. The raa7 mutant (RNA maturation of psaA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Recent results revealed that splicing of psaA-i1 and -i2 is assisted by at least two high molecular weight protein complexes (subcomplexes I and II) harboring the general splicing factor Raa1 together with intron-specific subunits (17,24). Here, we provide the first evidence for a high molecular weight apparatus involved in trans-splicing of the psaA mRNA, which is the first report of a high molecular weight splicing apparatus from a eukaryotic organelle.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Recent results revealed that splicing of psaA-i1 and -i2 is assisted by at least two high molecular weight protein complexes (subcomplexes I and II) harboring the general splicing factor Raa1 together with intron-specific subunits (17,24). Here, we provide the first evidence for a high molecular weight apparatus involved in trans-splicing of the psaA mRNA, which is the first report of a high molecular weight splicing apparatus from a eukaryotic organelle.…”
mentioning
confidence: 62%
“…A total of four independent TAP experiments were performed. Proteins were considered as specific if they were found in four separate biological replicates and not in control experiments (C1-C4) (17). These analyses revealed 19 putative Raa2-interacting proteins (supplemental Table S2).…”
Section: Core Components Of Trans-splicing Subcomplexes I and Ii-mentioning
confidence: 99%
See 3 more Smart Citations